Montelukast as Add-On Therapy to Inhaled Corticosteroids in the Management of Asthma (The SAS Trial) - J Mark FitzGerald; Sylvain Foucart; Stephen Coyle; John Sampalis; Denis Haine; Eliofotisti Psaradellis; R Andrew McIvor (Canadian Respiratory Journal)
AIM: To evaluate the effectiveness of montelukast as add-on therapy for asthmatic patients who remain uncontrolled with low, moderate or high doses of inhaled corticosteroid monotherapy.